Development of Resistant GvHD in a Patient Treated with Nivolumab for Hodgkins Lymphoma Relapse after Allogeneic Unrelated Transplantation - Steinerová, K; Jindra, P; Lysák, D; Karas, M (Klinicka onkologie, 2019)
BACKGROUND: Allogeneic hematopoietic stem cell transplantation is one of the therapeutic options for patients with relapsed or refractory classic Hodgkins lymphoma (cHL). In the case of dis-ease relapse after transplant, other treatment options are still limited (for example donor lymphocyte infusion, and chemother-apy with brentuximab, bendamustine, or other agents) with uncertain outcomes in terms of patient tolerance and long-term dis-ease remission. One way to achieve remission is administration of the PD-1 inhibitor nivolumab, a PD-1 checkpoint inhibitor. Nivolumab is also indicated for the treatment of cHL relapses after autologous hematopoietic stem cell transplantation. Since September 2018, nivolumab has been approved by the State Institute for Drug Control in the Czech Republic for treatment of cHL autologous hematopoietic stem cell transplantation relapse; however, treatment with nivolumab is accompanied by an increased risk of develop-ing fatal, acute graft-versus-host dis-ease. CASE: The article describes the development of resistant acute graft-versus-host disease in a patient who had received allogeneic-unrelated transplantation and nivolumab treatment for Hodgkins lymphoma relapse. CONCLUSION: Our case study, as well as the literature review, demonstrates the excellent efficacy of PD-1 inhibitors, but also cautions against the administration of these agents in patients follow-ing allogeneic hematopoietic stem cell transplantation. Administration of nivolumab to these patients should be done on a strictly individual basis in the context of known risks, and consideration should be given to other treatment options. Key words Hodgkins lymphoma -  PD-1 inhibitor -  nivolumab -  GvHD -  transplantation.
Keywords: antigeny CD279; Hodgkins lymphoma - PD-1 inhibitor - nivolumab - GvHD - transplantation; Hodgkinova nemoc; homologní transplantace; Nivolumab; nemoc štěpu proti hostiteli; protinádorové látky imunologicky aktivní; Graft vs Host Disease; Humans; Hodgkin Disease; Programmed Cell Death 1 Receptor; Recurrence; recidiva; Transplantation, Homologous; Antineoplastic Agents, Immunological; lidé; nivolumab